2012
DOI: 10.1177/0022034511435329
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Inhibits the Activity of Dental Cysteine Cathepsins

Abstract: The co-expression of MMPs and cysteine cathepsins in the human dentin-pulp complex indicates that both classes of enzymes can contribute to the endogenous proteolytic activity of dentin. Chlorhexidine (CHX) is an efficient inhibitor of MMP activity. This study investigated whether CHX could also inhibit cysteine cathepsins present in dentin. The inhibitory profile of CHX on the activity of dentin-extracted and recombinant cysteine cathepsins (B, K, and L) was monitored in fluorogenic substrates. The rate of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
150
0
25

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 32 publications
1
150
0
25
Order By: Relevance
“…40,68,70,71,72 It is well-known that certain substances are promising MMPs inhibitors, but the most studied in adhesive dentistry is chlorhexidine (CHX). 37,58,73,74 It is, in addition, also capable of inhibiting cysteine cathepsins (CCs) 75 the other key class of proteolytic enzymes identified in dentin. 76 CHX was accordingly shown to partially conserve the integrity of the hybrid layer, 77 , favoring bond durability.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…40,68,70,71,72 It is well-known that certain substances are promising MMPs inhibitors, but the most studied in adhesive dentistry is chlorhexidine (CHX). 37,58,73,74 It is, in addition, also capable of inhibiting cysteine cathepsins (CCs) 75 the other key class of proteolytic enzymes identified in dentin. 76 CHX was accordingly shown to partially conserve the integrity of the hybrid layer, 77 , favoring bond durability.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…As chlorhexidine possesses desirable MMP-inhibitory properties 16) and outstanding substantivity to human dentin 17,18) , it has been well studied as a MMP-inhibitor to prevent dentin bond degradation 13,14,[19][20][21][22][23][24][25][26] . Recent studies revealed that cysteine cathepsins are also present in intact and carious dentin which may also contribute to the breakdown of the exposed collagen in dentin hybrid layers 27,28) , and that chlorhexidine can also inhibits the activity of dentin cysteine cathepsins 29) . Although the effect of chlorhexidine on the bond durability of coronal dentin to resin is well studied, few studies have evaluated the effect of chlorhexidine application on the bond durability of radicular dentin to resin.…”
Section: Introductionmentioning
confidence: 99%
“…CHX effectively inhibits MMP-2, -8 and -9 (13,16,17) and cysteine cathepsins (18). In addition, many studies have demonstrated that CHX may improve the structural stability of collagen matrix in the hybrid layer and decrease time-dependent reduction in resin-dentin bond strength (14,17,19,20).…”
Section: Discussionmentioning
confidence: 99%